Chitosan-Gentamicin Conjugate Hydrogel Promoting Skin Scald Repair - Tingting Yan; Songzhi Kong; Qianqian Ouyang; Chengpeng Li; Tingting Hou; Yu Chen; Sidong Li (Marine Drugs, 2020)
Our earlier research indicated that chitosan-gentamicin conjugate (CS-GT) possesses superior antimicrobial activity and good water solubility. To develop CS-GT-based scald dressings, the antibacterial properties of CS-GT were further studied, and the biosafety of CS-GT and the healing mechanism of CS-GT hydrogel was systematically explored in this article. It was found that cell viability shows a declined inclination with the prolonged culture time and the increased concentration of CS-GT. After three day’s culture, the cell viability could still remain at 79.72% when CS-GT concentration was as high as 1000 μg/mL. On the other hand, the hemolysis rate of CS-GT was lower than 5% when its concentration is 800 μg/mL. Therefore CS-GT has good cytocompatibility and hemocompatibility. A wound-healing experiment has shown that the skin healing rate of CS-GT hydrogel was the highest at 99.61%, followed by the positive control (wet burn ointment) 94.98%, GT hydrogel 87.50%, and matrix 77.39%. The blank control group, however, possessed the lowest healing rate of 75.45%. Further analysis indicated that CS-GT hydrogel could promote the synthesis of total protein (TP) in skin granulation tissue, resulting in the enhanced hydroxyproline (HYP) content, which facilitated collagen fibrogenesis, reduced cytokine expression in an inflammatory response, and, ultimately, accelerated wound healing. To sum up, CS-GT hydrogel is a promising scald dressing.